THEORETICAL ESTIMATION OF DISSOLVING IN BOWL OF THE POWDER CARBONIC MATERIALS, USED IN STEELMAKING OF RUP “BMZ” - A. N. Chichko; N. V. Andrianov; S. V. Terletski; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия)
The dynamics of dissolving at stirring by argon of carbonic powders, being produced by different suppliers of BMZ, is determined on the basis of computer modeling. The integral dependencies of the carbon changing in melt and of the carburizers mass on period of stirring for powders of different breakup are calculated. The criterion of dissolution of carbonic powder in steel melt is offered.